How and why did MARS facilitate migration control? Understanding the implication of migration and refugee studies (MARS) with the restriction of human mobility by UK state agencies - Hatton, J (2011)
This thesis makes two related arguments regarding the academic field of migration and refugee studies (MARS) and the control of migration by UK state agencies. The first, and more empirical one, is that the former facilitated the latter: the field’s members provided symbolic, technical, and pedagogic assistance to two non-departmental public bodies in controlling migration. The second, and more theoretical, argument of this thesis is that MARS facilitated migration control because of culture, power, and structure. It is through the field’s implication in the coercion of its human subjects by UK state agencies that MARS academics a) answered their calling, b) assisted class rule as ideologists, and c) separated sacred and profane by policing endogamy. The introduction describes the existing literature on the relationship between MARS and migration control. The consensus is that the former facilitated the latter. However, these studies fail to provide detailed accounts of the ways in which it did so. Chapter One defines the elements of my more empirical argument: MARS and migration control. An historical narrative outlines the institutional development of the field since its beginnings in the early 1980s. Then a new model for understanding migration control – i.e., migrant CODAR – is described. Chapter Two uses this model to trace the actor network through which MARS academics facilitated the restriction of their human subjects’ mobility by the UK state agencies of the Advisory Panel on Country Information and the Migration Advisory Committee. Chapters Three, Four, and Five use Weberian, Marxist, and Durkheimian anthropological approaches (respectively) to explain the implication of MARS and migration control that is described in Chapters One and Two. Finally, the conclusion of the thesis discusses its contributions to both more particular (i.e., the literature surveyed in the introduction on MARS and migration control) and more general (i.e., anthropology) scholarly fields.